COMPARISON OF FAMILY LAW SYSTEMS IN THE UNITED STATES, INDONESIA, AND FRANCE: A CASE STUDY OF MARRIAGE AND DIVORCE RULES - Sofyan Mei Utama; Diana Farid; Trisulo Trisulo; Achmad Siddiq; Nahdia Nazmi (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
Family law systems in different countries significantly differ between marriage and divorce regulations. This research aims to compare the family law systems in several selected countries and analyze the marriage and divorce regulations in these countries. The research method used is qualitative with a case study approach. At the same time, primary and secondary data are obtained from literature studies where the retrieval process is from various trusted sources such as journals, books, and legal regulations. Data analysis uses descriptive analysis of research methods by collecting data after the actual data is compiled, processed, and analyzed to provide an overview of the existing problems. The results show that the selected countries, namely the United States, France, and Indonesia, have different marriage requirements, divorce proceedings, property division, and child custody regulations. An in-depth discussion of these differences provides a better understanding of the family law system in each country and its implications for individuals involved in the marriage and divorce process. This research concludes that comparing family law systems in different countries opens up room for developing better regulations to protect the interests of individuals and families in the context of marriage and divorce.